Mitochondrial complex I activity and oxidative damage to mitochondrial proteins in the prefrontal cortex of patients with bipolar disorder - Andreazza, Ana C; Shao, Li; Wang, Jun-Feng; Young, L Trevor (Archives of general psychiatry, 2010)
Accumulating evidence suggests that mitochondrial dysfunction and oxidative stress contribute to the pathogenesis of bipolar disorder and schizophrenia. It remains unclear whether mitochondrial dysfunction, specifically complex I impairment, is associated with increased oxidative damage and, if so, whether this relationship is specific to bipolar disorder. To evaluate whether decreased levels of the electron transport chain complex I subunit NDUFS7 are associated with complex I activity and increased oxidative damage to mitochondrial proteins in the prefrontal cortex of patients with bipolar disorder, schizophrenia, or major depressive disorder. Postmortem prefrontal cortex from patients and controls were assessed using immunoblotting, spectrophotometric, competitive enzyme immunoassay to identify group differences in expression and activity of complex I, and in oxidative damage in mitochondria. University of British Columbia, Vancouver, Canada. Patients Forty-five patients with a psychiatric disorder (15 each with bipolar disorder, schizophrenia, and major depressive disorder) and 15 nonpsychiatric control subjects were studied. Oxidative damage to proteins and mitochondrial complex I activity. Levels of NDUFS7 and complex I activity were decreased significantly in patients with bipolar disorder but were unchanged in those with depression and schizophrenia compared with controls. Protein oxidation, as measured by protein carbonylation, was increased significantly in the bipolar group but not in the depressed or schizophrenic groups compared with controls. We observed increased levels of 3-nitrotyrosine in the bipolar disorder and schizophrenia groups. Impairment of complex I may be associated with increased protein oxidation and nitration in the prefrontal cortex of patients with bipolar disorder. Therefore, complex I activity and mitochondrial dysfunction may be potential therapeutic targets for bipolar disorder.